Implementasi Knowledge Management di SMP Ta’mirul Islam Surakarta - Faiz, Muhammad Noor; Rahmawati , Aninda; Nurhuda, Abid; Huda, Ali Anhar Syi'bul (Jaanur Elbarik Indonesia, 2025)
This study aims to determine how the implementation includes planning, organizing, implementing, and controlling knowledge management at Ta'mirul Islam Junior High School in Surakarta. The method used in this research is descriptive qualitative, namely by collecting data through observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman model where the data is collected, then reduced, presented, and drawn verification conclusions with triangulation. The results of this study show that the planning stage is carried out during the year-end meeting activities and routine meetings every week, and then a policy related to knowledge management is produced. Teachers prepare teaching plans or lesson plans according to agreed policies. Then the organizing stage is realized through the formation of a clear division of tasks and authority structure, the committee of an intracurricular and extracurricular activity, guidance from the principal, and the preparation of teaching materials by the teacher. Furthermore, the Actuating stage tends to be the process of transferring knowledge between teachers and students such as teachers conducting KBM activities using methods/strategies according to the conditions of the students and the last is Controlling with a two-way evaluation such as the principal assessing the performance of school components and teachers evaluating the performance of the school